Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1038/nmat4563
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic toroidal excitations in matter and free space

Abstract: The toroidal dipole is a localized electromagnetic excitation, distinct from the magnetic and electric dipoles. While the electric dipole can be understood as a pair of opposite charges and the magnetic dipole as a current loop, the toroidal dipole corresponds to currents flowing on the surface of a torus. Toroidal dipoles provide physically significant contributions to the basic characteristics of matter including absorption, dispersion, and optical activity. Toroidal excitations also exist in free-space as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
444
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 491 publications
(462 citation statements)
references
References 79 publications
(116 reference statements)
9
444
0
Order By: Relevance
“…Previously it was shown that such type of interference, the socalled anapole mode 31,32 , could be observed in Si nanodisks. For nanodisks, this anapole mode can be achieved at a specific wavelength and for some fixed ratio of the disk height to its diameter.…”
Section: High-index Dielectric Particlesmentioning
confidence: 99%
“…Previously it was shown that such type of interference, the socalled anapole mode 31,32 , could be observed in Si nanodisks. For nanodisks, this anapole mode can be achieved at a specific wavelength and for some fixed ratio of the disk height to its diameter.…”
Section: High-index Dielectric Particlesmentioning
confidence: 99%
“…Our group reported the observation of the dynamic anapole in a microwave metamaterial in 2013 [125]. The observation of a resonant toroidal response in metamaterials has enabled the systematic study of toroidal electrodynamics [126]. Despite the recent stream of experimental and theoretical works, however, the field is still in its infancy, with many questions to be resolved and applications to be explored.…”
Section: Developing Metamaterials Technology: Switching and Tunabilitymentioning
confidence: 99%
“…FD pulses can be seen as propagating counterparts of the localized toroidal dipole excitations in matter [11]. The toroidal dipole is distinct from the conventional electric and magnetic dipoles [12,13] and have attracted significant interest in recent years as important contributors to the electromagnetic properties of media with non-local response or elements of toroidal symmetry [11,[14][15][16][17][18][19][20][21]. Superposition of dynamic electric and toroidal dipoles leads to anapoles which, through destructive interference, exhibit vanishing radiated fields outside the source [20,22].…”
mentioning
confidence: 99%
“…They are necessarily few-cycle, wideband electromagnetic perturbations with toroidal field topology that can exist in transverse electric (TE) and transverse magnetic (TM) configurations [1,10]. FD pulses can be seen as propagating counterparts of the localized toroidal dipole excitations in matter [11]. The toroidal dipole is distinct from the conventional electric and magnetic dipoles [12,13] and have attracted significant interest in recent years as important contributors to the electromagnetic properties of media with non-local response or elements of toroidal symmetry [11,[14][15][16][17][18][19][20][21].…”
mentioning
confidence: 99%